ANALISIS PENGARUH KONDISI FISIK LINGKUNGAN KERJA DAN FAKTOR PSIKOLOGI TERHADAP KINERJA KARYAWAN PT. XYZ - Reini Auliya; Masdania Zuraiah; Rizka Rida; Rahmad Rezeki (Journal of Innovation Research and Knowledge, 2025)
The purpose of this study was to determine the effect of physical conditions and psychological factors partially and simultaneously on employee performance at PT. XYZ. This type of research is quantitative research with a causal research design. The population of this study were all employees of PT. XYZ. The sample of this study was 20 employees of PT. XYZ. Data collection used primary data measured directly by an independent laboratory and secondary data obtained from company documents related to this study. using multiple linear regression analysis and the data obtained will be inputted into minitab. Based on the multiple linear regression test, it can be seen that there is a negative influence between psychology and employee performance with a regression coefficient of 0.00165, meaning that if psychology increases by 1%, ployee performance decreases by 0.00165% based on the F test to see whether the independent variable has a significant relationship overall with the dependent variable, using ɑ = 5% or 0.05, testing is carried out simultaneously. the data obtained has an F value of 1.72 using ɑ = 5% obtained a p value of 0.009 while in the T test using minitab it is seen that the p value is below ɑ = 0.05 which means that we can reject. Therefore, the four parameters are statistically significant.